2015
DOI: 10.1136/annrheumdis-2015-eular.1903
|View full text |Cite
|
Sign up to set email alerts
|

FRI0488 Prevalence and Clinical Significance of Cognitive Impairment in Systemic Sclerosis

Abstract: Scientific AbstractsFriday, 12 June 2015 605Finally, in SSc patients LVEF inversely correlated with disease duration (R=-0.3, p=0.035) and number of ventricular ectopic beats (VEBs) on 24h-ECG Holter (R=-0.3, p=0.04). Interestingly, considering the right ventricle, the number of VEBs inversely correlated also with EF (R=-0.4, p=0.04) and directly correlated with EDV (R=0.4, p=0.01) and ESV (R=0.5, p=0.002). Conclusions: CMRI could be a useful tool to detect abnormal ventricular function and volumes and allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…More than half (56%) of participants experienced mild‐to‐severe cognitive impairment in our study. Contrary to previous research (24), we found that older age was significantly associated with better perceived cognitive function. Because older participants were mostly retired, their daily life tasks might not require much cognitive capability compared with working‐age participants.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…More than half (56%) of participants experienced mild‐to‐severe cognitive impairment in our study. Contrary to previous research (24), we found that older age was significantly associated with better perceived cognitive function. Because older participants were mostly retired, their daily life tasks might not require much cognitive capability compared with working‐age participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Perceived cognitive dysfunction in patients with SSc is prevalent (21,22,24,25); however, this domain is not well understood. This study is among the first to examine how demographic characteristics, SSc characteristics, and symptoms experienced relate to perceived cognitive function in people with SSc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations